2021
DOI: 10.1126/scitranslmed.abf7517
|View full text |Cite
|
Sign up to set email alerts
|

T cell and antibody kinetics delineate SARS-CoV-2 peptides mediating long-term immune responses in COVID-19 convalescent individuals

Abstract: Long-term immunological memory to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is crucial for the development of population-level immunity, which is the aim of vaccination approaches. Reports on rapidly decreasing antibody titers have led to questions regarding the efficacy of humoral immunity alone. The relevance of T cell memory after coronavirus disease 2019 (COVID-19) remains unclear. Here, we investigated SARS-CoV-2 antibody and T cell responses in matched samples of COVID-19 convalescent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
151
1
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(168 citation statements)
references
References 85 publications
12
151
1
4
Order By: Relevance
“…In line with our results, several recent studies also reported that the T-cell responses to SARS-CoV-2 were maintained in patients up to 6 months after the onset of COVID-19 symptoms. [22][23][24] However, another group found that the frequencies of spike-specific CD4 + T cells declined in the first 4 months POS. 25 Indeed, in our study, either CD4 + or CD8 + T-cell response waned in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, several recent studies also reported that the T-cell responses to SARS-CoV-2 were maintained in patients up to 6 months after the onset of COVID-19 symptoms. [22][23][24] However, another group found that the frequencies of spike-specific CD4 + T cells declined in the first 4 months POS. 25 Indeed, in our study, either CD4 + or CD8 + T-cell response waned in some patients.…”
Section: Discussionmentioning
confidence: 99%
“…In order to control future outbreaks and identify at-risk individuals, the exact constituents of effective COVID-19 immunity at a population level must be understood. When used alongside measurements of virus-specific antibodies, T cell response readouts represent a powerful, additional measure of potential immunity from COVID-19, with a higher degree of confidence than either measurement on their own, in particular given the concern on the longevity of measurable antibody responses (21)(22)(23). In addition, the FDA's decision to issue emergency use authorisation for a SARS-CoV-2 T cell test highlights the growing acceptance and usefulness of T cell testing for the clinical management of certain patient groups (24).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on immunological responses against SARS-CoV-2 provided a detailed picture of immune signatures in COVID-19 patients (either with severe disease, mildly symptomatic or asymptomatic) as compared to convalescent individuals, people that have been in close contact with a COVID-19 patient, and unexposed healthy donors. Such studies consistently reported a major role of T cell responses in developing immunity against SARS-CoV-2 [ 53 , 55 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. Notably, T cell responses were shown to be polyfunctional (involving both CD4+ and CD8+ lymphocytes), stable, and lasting for at least six months after infection, even though anti-SARS-CoV-2 antibodies decline with time [ 63 , 65 , 69 ].…”
Section: Do Repeated Exposures To Low Sars-cov-2 Doses Induce T Cell Immunity? a Possible Explanation For Sars-cov-2-specific T Cell Respmentioning
confidence: 95%
“…Such studies consistently reported a major role of T cell responses in developing immunity against SARS-CoV-2 [ 53 , 55 , 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. Notably, T cell responses were shown to be polyfunctional (involving both CD4+ and CD8+ lymphocytes), stable, and lasting for at least six months after infection, even though anti-SARS-CoV-2 antibodies decline with time [ 63 , 65 , 69 ]. Moreover, SARS-CoV-2-specific T cells with a stem-like memory phenotype (CCR7+CD127+CD45RA−/+TCF1+) were identified in COVID-19 convalescent subjects, even in the absence of detectable circulating antibodies, highlighting the role of memory T cells in sustaining long-term immunity against SARS-CoV-2 [ 67 ].…”
Section: Do Repeated Exposures To Low Sars-cov-2 Doses Induce T Cell Immunity? a Possible Explanation For Sars-cov-2-specific T Cell Respmentioning
confidence: 95%